Challenges facing artists and institutions when showcasing and collecting internet art: a comparative study - Vezi, Mazwi (My University, 2011)
Internet Art is an art form that uses the Internet as its primary medium from its production to presentation. Internet Art characteristics and attributes bring about presentation, preservation and colleting challenges to the curatorial practice; especially if presented in a museum or gallery structure. Strategies used by early Internet Artists were influenced by the characteristics of this medium; these are variability and technological obsolescence. Internet Art is inherently process based, ubiquitous, ephemeral and dynamic in nature. This challenges the traditional role of the curator in a gallery and museum structure. The curator is increasingly expected to create platforms of exchange of ideas between the viewer of the artwork and the project itself. Additional the curator also has to provide some insight in the decision making process regarding maintenance, support, contracts and documentation. Internet Art questions the principles in which galleries and museum structures are based; these include objectification, not touching objects and authorship of Internet Art projects. These projects are collaborative in nature and created by more than one artist, normally geographically dispersed. Internet Art demand for new modes of presentation, documentation and preservation that are more suited for online art. These new modes of presentation fundamentally change the role of the curator. If galleries and museums want to start or continue growing their Internet Art collections, they need to start understanding challenges facing the Internet as a medium, develop appropriate presentation and preservation strategies that seek to address identified challenges.